2020
DOI: 10.1101/2020.10.16.334714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of MGA mediated Polycomb repression promotes tumor progression and invasiveness

Abstract: MGA, a transcription factor and member of the MYC network, is mutated or deleted in a broad spectrum of malignancies. As a critical test of a tumor suppressive role, we inactivated Mga in two mouse models of non-small cell lung cancer using a CRISPR based approach. MGA loss significantly accelerated tumor growth in both models and led to de-repression of atypical Polycomb PRC1.6, E2F and MYC-MAX targets. Similarly, MGA depletion in human lung adenocarcinoma lines augmented invasive capabilities. We further sh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Its structure allows the regulation of both MAX-network and T-domain target genes, either as an activator or repressor [ 6 , 7 , 8 ]. Inactivation of MGA is frequent in human cancer, and a recent study has demonstrated that MGA functions as a tumor suppressor in murine models of lung carcinoma and in colorectal cancer organoids, partly due to the de-repression of MYC target genes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its structure allows the regulation of both MAX-network and T-domain target genes, either as an activator or repressor [ 6 , 7 , 8 ]. Inactivation of MGA is frequent in human cancer, and a recent study has demonstrated that MGA functions as a tumor suppressor in murine models of lung carcinoma and in colorectal cancer organoids, partly due to the de-repression of MYC target genes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The next probe cg07713411 is near gene MGA. MGA has been widely reported to be associated with tumor invasion ( 43 ) and progression ( 44 ). MGA has also been reported to contribute to MYC-mediated pathway in colorectal cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…SNV analysis gives similar results with literature for example EGFR and KRAS mutations are mutually exclusive in LUAD samples that is confirmed again [ 9 ]. Additionally, EGFR [ 102 ], MGA [ 103 ], SMARCA4 [ 104 ], ATM [ 105 ], RBM10 [ 106 ] and KDM5C [ 107 ] which are lung cancer related genes are mutated only in LUAD but not in LUSC. On the other hand, CDKN2A [ 108 ], PTEN [ 109 ] and HRAS [ 110 ] genes are mutated only in LUSC.…”
Section: Discussionmentioning
confidence: 99%